2004
DOI: 10.1111/j.1365-201x.2004.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice for studies of the renin–angiotensin system in hypertension

Abstract: Hypertension is a polygenic and multi-factorial disorder that is extremely prevalent in western societies, and thus has received a great deal of attention by the research community. The renin-angiotensin system has a strong impact on the control of blood pressure both in the short- and long-term, making it one of the most extensively studied physiological systems. Nevertheless, despite decades of research, the specific mechanisms implicated in its action on blood pressure and electrolyte balance, as well as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…21 For instance, it has been shown that endothelial dysfunction is present and that increased oxidative stress in this model also contributed to the vascular dysfunction. 38 We can, thus, hypothesize that endothelial dysfunction may also be present in the female R ϩ A ϩ mice and may, therefore, contribute to the development of SPE symptoms in this model.…”
Section: Male Rmentioning
confidence: 99%
See 1 more Smart Citation
“…21 For instance, it has been shown that endothelial dysfunction is present and that increased oxidative stress in this model also contributed to the vascular dysfunction. 38 We can, thus, hypothesize that endothelial dysfunction may also be present in the female R ϩ A ϩ mice and may, therefore, contribute to the development of SPE symptoms in this model.…”
Section: Male Rmentioning
confidence: 99%
“…[17][18][19][20] Indeed, male mice have elevated blood pressure, Ϸ150 mm Hg, 17 and show high plasma levels of Ang II with evidence of end-organ damage, such as endothelial dysfunction. 21 Although these phenotypes have not been characterized in females, they should be similar, because transgene expression is equivalent. Therefore, because chronic hypertension is an important risk factor for PE, 22 we hypothesized that hypertensive R ϩ A ϩ double-transgenic female mice would develop SPE, and, therefore, we propose these mice as an animal model of this clinical reality.…”
mentioning
confidence: 99%
“…Although the compensatory hyperinsulinemia that results from IR temporarily delays the development of diabetes, as demonstrated in rat studies, it has other effects that may ultimately increase blood pressure (BP) [4]. Hyperinsulinemia promotes reabsorption of sodium and water in proximal renal tubules, leading to volume expansion and BP increase [4], which may amplify SNS activity [12] and may activate the RAAS [21,22]. However, there is no direct experimental evidence suggesting that corrections in these defects of insulin action will decrease BP; this remains a challenge for the clinician/researcher to prove "cause and effect".…”
Section: Compensatory Hyperinsulinemiamentioning
confidence: 99%
“…81 Evidence supports that local Ang II synthesis occurs in select tissues. [82][83][84][85] Tissues expressing all or most of the components of a local RAS include the heart, smooth muscle vasculature cells, kidney, brain, adrenal gland, pancreas, placenta, testes and adipose tissue. Overexpressing RAS genes in animals and RAS knockout models have allowed investigators to detail the presence and function of a local RAS in a variety of tissues.…”
Section: Effects Of Local Renin-angiotensin System I Presence Of Locmentioning
confidence: 99%
“…Overexpressing RAS genes in animals and RAS knockout models have allowed investigators to detail the presence and function of a local RAS in a variety of tissues. [82][83][84][86][87][88] Local RAS primarily exerts autocrine and paracrine actions via Ang II activation of the tissue-specific Ang II type 1 receptor. 89 It also interacts with the endocrine RAS and other peptides on multiple levels.…”
Section: Effects Of Local Renin-angiotensin System I Presence Of Locmentioning
confidence: 99%